2002
DOI: 10.2298/jas0202179z
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol content in meat of some Cyprinidae

Abstract: The aim of this paper was to examine cholesterol content in meat of five Cyprinidae species: white bream (Bllica bjoerkna L), carp bream (Abramis brama L), baltic vimba (Vimba vimba carinata Pallas), zope (Abramis balerus L) and crucian carp (Carassius carassius gibelio Bloch) from the river Danube. Cholesterol content was examined in the function of season factor and individual weight. Cholesterol concentration in meat of white bream carp bream, baltic vimba, zope and crucian carp is on average level below 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Kandungan kolesterol fillet ikan kakap merah segar adalah 20 mg/ 100 g. Hasil ini lebih rendah dibandingkan Mathew et al (1999) yaitu sebesar 95,5 mg/ 100 g. Pada fillet ikan kakap merah goreng kandungan kolesterol mengalami perubahan menjadi 60 mg/ 100 g. Zivkovic et al (2002) menyatakan kandungan kolesterol pada ikan dipengaruhi oleh spesies, jenis kelamin, musim, nutrisi pakan dan kandungan asam lemak tak jenuh majemuk.…”
Section: Asam Lemak Fillet Ikan Kakap Merahunclassified
“…Kandungan kolesterol fillet ikan kakap merah segar adalah 20 mg/ 100 g. Hasil ini lebih rendah dibandingkan Mathew et al (1999) yaitu sebesar 95,5 mg/ 100 g. Pada fillet ikan kakap merah goreng kandungan kolesterol mengalami perubahan menjadi 60 mg/ 100 g. Zivkovic et al (2002) menyatakan kandungan kolesterol pada ikan dipengaruhi oleh spesies, jenis kelamin, musim, nutrisi pakan dan kandungan asam lemak tak jenuh majemuk.…”
Section: Asam Lemak Fillet Ikan Kakap Merahunclassified
“…The total cholesterol content in the meat of fish depends on the species, age, sex, spawning cycle, harvesting period and geographical location of the reservoir (Donmez, 2009;Komprda et al, 2003;Piironen et al, 2002;Živković et al, 2002). Bieniarz et al (2001) confirmed a statistically significant differences in the total cholesterol content in the meat of some line of carp (Cyprinus carpio L.) depending on the age and season.…”
Section: Introductionmentioning
confidence: 99%